PERFORMANCE OF SESAMUM VARIETIES UNDER RAINFED UPLAND CONDITIONS IN THE N-E GHAT ZONE OF ODISHA - A. Mishra; S. K. Mohanty; B. Behera; S. Mishra; K. C. Samal A. K. Mukherjee; S. Das (Journal of Animal and Plant Sciences, 2018)
Sixteen sesamum genotypes were evaluated for their yield performance as well as inter-relationship among morphological traits and genetic diversity. Very low genetic advance was observed for dry biomass and seed yield showing that expression of both the characters is highly influenced by environment. High heritability coupled with high genetic advance as found in characters like capsules/plant and seeds/capsule indicates that heritability was due to additive gene effects and selection may be helpful. The genotypes differed from each other with respect to their reaction to different insect pests and diseases. Incidence of phyllody was noticed in only 3 genotypes ranging from 0.2% in Kalika to 1.0% in Maghi Local. Significantly high positive correlation was observed between days to 50% flowering and maturity which clearly shows that early flowering types can be chosen for early maturity. Both these characters exhibited significantly high positive correlation with plant height, branches/plant and incidence of phyllody. No significant association was observed for any trait with seed yield although the direction and magnitude of correlation coefficients varied. The local type, Maghi Local was found to be most divergent from rest of the genotypes and thus could be utilized in hybridization-based crop improvement programmes. Two genotypes, OSC-24 (95)-2-1-3 and OSC- 539 were found to be very close to each other showing least divergence. The varieties, Prachi and OSSel 84 produced average seed yield of more than 4.0 q/ha and were, therefore, found most suitable for the N-E Ghat zone of Odisha. Other varieties which exhibited satisfactory yield (about 3.5 q/ha) were Kanak and Nirmala which could also be profitably cultivated in this agro-climatic zone. global area and production) among more than fifty
Keywords: Sesamum; varietal performance; character association; genetic diversity